In Situ Detection of Adenovirus DNA and mRNA in Individual Cells. Issue 1 (27th April 2018) - Punga, Tanel; Ciftci, Sibel; Nilsson, Mats; Krzywkowski, Tomasz
Abstract: Infection by DNA viruses such as human adenoviruses (HAdVs) causes a high‐level accumulation of viral DNA and mRNA in the cell population. However, the average viral DNA and mRNA content in a heterogeneous cell population does not inevitably reflect the abundance in individual cells. As the vast majority of virus infection studies is carried out using standard experimental procedures with heterogeneous cell populations, there is a need for a method allowing simultaneous detection and quantitative analysis of viral genome accumulation and gene expression in individual infected cells within a population. This article describes a padlock probe–based rolling‐circle amplification protocol that allows simultaneous detection of HAdV type 5 (HAdV‐5) DNA and various virus‐encoded mRNAs, as well as quantitative analysis of HAdV‐5 DNA copies and mRNA species, in individual cells within a heterogeneous population. This versatile method can be used to detect the extent of pathogenic DNA virus infection in different cell types over prolonged infection times. Furthermore, simultaneous viral DNA and mRNA quantification in individual cells allows identification of cells in which persistent infections may be established. © 2018 by John Wiley & Sons, Inc.